Menakar Peran Utang Luar Negeri Terhadap Kinerja Ekonomi Makro Negara Berkembang - Acuviarta; Sidik Priadana; Muhammad Thoriq Al Zyad (Jurnal Riset Ilmu Ekonomi, 2021)
This study was conducted to analyze the factors that affect foreign debt and the impact of foreign debt on Asean economic growth in 2008-2017. This study uses two tests, the first test uses the Granger causality test, the second test uses a panel data regression test. Granger causality test results show that there is no one-way or two-way relationship between economic growth and foreign debt, and vice versa. The result of the second test, which is panel data regression, shows that the exchange rate, interest rate and government spending variables have a significant negative effect on foreign debt, the export variable has a significant positive effect on foreign debt, while the investment variable has an insignificant negative effect on foreign debt.